2018
DOI: 10.1080/10286020.2018.1488830
|View full text |Cite
|
Sign up to set email alerts
|

A new diphenolic metabolite isolated from the marine-derived fungus Aspergillus niger 102

Abstract: A new diphenolic derivative asperdiphenol A (1), along with nine known compounds (2-10), was isolated from the marine-derived fungus Aspergillus niger 102. Their structures were elucidated on the basis of spectroscopic analysis including NMR and MS spectrometry. Compound 1 was suggested to be a chiral mixture by the specific rotation and chiral HPLC. Compound 1 was evaluated for its anti-inflammatory, antibacterial, and cytotoxic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, it was found that the COVID-19 mortality rate in breast cancer patients depends more on comorbidities than prior radiation therapy or current anti-cancer treatment [9]. Currently, breast cancer is the leading (30%) common cancer and the second (23%) cause of cancer death among women, which is considered as a top killer for women [10]. Therefore, these patients need to take additional precautions against the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that the COVID-19 mortality rate in breast cancer patients depends more on comorbidities than prior radiation therapy or current anti-cancer treatment [9]. Currently, breast cancer is the leading (30%) common cancer and the second (23%) cause of cancer death among women, which is considered as a top killer for women [10]. Therefore, these patients need to take additional precautions against the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds isolated from Aspergillus niger caught a lot of attention because of their chemical diversities and significant biological activity. Fumonisins, naptho‐γ‐pyrones (NGPs), bicoumarins, asperazines and malformins are important secondary metabolites from A. niger , [ 3 ] which displayed significant biological activity including antimicrobial [ 4 ] and antitumour effects. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%